A cost-benefit analysis of electricity supply in a developing country, with reference to Venda - Themeli, Tshimangadzo Booi (Rhodes University, Faculty of Commerce, Department of Economics, 1992)
This study concentrates specificaUy on assessing those elements of private and external costs and benefits which need to be accounted for in analyzing the role of electricity supply in a developing region. To facilitate this aim, three interrelated questions are addressed. The first question examines the reasons why a critical need for electrification in developing areas exists. In this regard, a selective review of the literature on development economics is offered, illuminating the previous neglect of the rural dimension in development and the associated problems of poverty and inequality, a lack of infrastructure and the general inability to fulfill basic needs. The second question is devoted exclusively to an economic analysis of the supply of electricity in developing areas. A broad theoretical review on whether an unregulated or regulated (private or public) sector should be responsible for the provision of electrification is presented. This evaluation highlights the various welfare implications and efficiency considerations that appear to be relevant in the present context. The final question, which constitutes the central proposition of the thesis, establishes how electrification should be supplied in developing areas. To this end, the conditions specific to a region in Venda are discussed. An attempt is made to identify the private and external costs and benefits relating to electricity supply and the corresponding costs and benefits pertaining to alternative sources of energy. Since the incidence and nature of these costs and benefits could only be ascertained from individual households, it was deemed necessary to undertake a questionnaire study of residents in Makwarela township and its periurban settlement of Lufule-Tshisele. A number of basic trends were evident from the research results. As far as the various benefits are concerned, respondents tended to place a much higher value on both the private and external benefits associated with electricity than its alternatives. At the same time, the survey found that although the private (or monetary) cost of electricity far exceeded the corresponding cost of alternative energy sources, the external costs were significant in the case of alternative energy sources, but virtually non-existent in the case of electricity. On the whole, the Venda survey seems to suggest that an economic case can be made for involving the broader community in subsidising the supply of electricity in Makwarela, Lufule-Tshisele and other areas. While such a subsidy can perhaps be justified on distribution grounds alone, and more specifically in terms of the rapid and pronounced effect it is likely to have on the quality of life in the region, its real worth lies in the fact that it may confer certain external benefits on the community.
Keywords: Electrification -- Economic aspects -- South Africa -- Venda; Electric utilities -- South Africa -- Venda; Cost effectiveness; Electrification -- Cost effectiveness